Methods to determine the stress intensity factor (2019)
This paper presents a brief review of the existing methods to determine the stress intensity factor. Some historical aspects of fracture mechanics are presented. Then some of the methods are described, classifying them into three groups: analytical, finite element, and experimental methods. For each method, its characteristics, advantages, disadvantages, and restrictions are discussed. The reasons for the scientific community to advance in the application of the finite element method, due to its great versatility, are evident. It is clear that learning, mastering, and applying any of the methods entails a great effort.